Pengaruh Metode Tutor Sebaya terhadap Peningkatan Kemampuan Analisis Statistik Guru Bahasa Inggris di Kabupaten Sampang - Dedi Siolimbona; Salman Alfarizi Pradana Andika Putra; Haerussaleh Haerussaleh (Universitas Islam Jember, 2026)
This study aims to analyze the impact of the peer tutoring method on improving the statistical analysis skills of English teachers in Sampang Regency. The peer tutoring method was selected as an alternative collaborative learning strategy expected to provide teachers with an effective platform to share experiences and knowledge. A pre-experimental design specifically a one-group pretest-posttest design was employed for this study. The research subjects were English teachers in Sampang Regency participating in a training program. Data were collected through tests and observations. Data analysis involved normality testing and hypothesis testing using a paired-sample t-test. The findings indicate that the implementation of the peer tutoring method enhanced the teachers' statistical analysis skills. Hypothesis test results showed a significance value below 0.05, alongside an increase in participants' average scores. Thus, the peer tutoring method proved effective in improving the statistical analysis capabilities of English teachers in Sampang Regency. The study concludes that the peer tutoring method serves as an effective approach for enhancing teachers' professional competence, particularly regarding statistical analysis. These findings are expected to serve as a reference for the development of future teacher training programs. Keywords: Peer Tutoring, Statistical Analysis, English Teacher